2016
DOI: 10.1128/genomea.00372-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Vaccinia Virus Strain L-IVP

Abstract: Most of the live vaccine doses of vaccinia virus donated to the Intensified Smallpox Eradication Programme after 1971 were prepared using the L-IVP strain. A mixture of three clones of the L-IVP strain was sequenced using MySEQ. Consensus sequence similarity with the vaccinia virus Lister strain is 99.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Сообщалось, что штамм Lister кодирует больше генов, участвующих в уклонении от иммунного ответа, таких как A53R, рецептор растворимого фактора некроза опухоли, или T1/35 кДаингибитор CC-хемокинов, которые отсутствуют в других штаммах, таких как MVA или WR (Western Reserve) [9,10]. LIVP является биовариантом английского штамма Lister, полученным путем его адаптации в коже теленка [11]. Этот штамм частично использовали в программе ликвидации оспы после 1971 г., и, как сообщается, он обладает онколитическими свойствами и значительно меньшей вирулентностью по сравнению с другими биовариантами штамма Lister [12,13], кроме этого, он не был изучен в ряде доклинических и клинических исследований [14][15][16][17][18][19].…”
Section: Bulletin Of Rsmu 2 2023 Vestnikrgmuru | |unclassified
“…Сообщалось, что штамм Lister кодирует больше генов, участвующих в уклонении от иммунного ответа, таких как A53R, рецептор растворимого фактора некроза опухоли, или T1/35 кДаингибитор CC-хемокинов, которые отсутствуют в других штаммах, таких как MVA или WR (Western Reserve) [9,10]. LIVP является биовариантом английского штамма Lister, полученным путем его адаптации в коже теленка [11]. Этот штамм частично использовали в программе ликвидации оспы после 1971 г., и, как сообщается, он обладает онколитическими свойствами и значительно меньшей вирулентностью по сравнению с другими биовариантами штамма Lister [12,13], кроме этого, он не был изучен в ряде доклинических и клинических исследований [14][15][16][17][18][19].…”
Section: Bulletin Of Rsmu 2 2023 Vestnikrgmuru | |unclassified
“…Vaccinia virus Lister strain from the Institute of Virus Preparation, Moscow, Russia (LIVP) is an attenuated variant reported to hold excellent oncolytic properties. 18 , 19 , 20 , 21 Previously, it was demonstrated that this strain could treat highly immunosuppressive tumors such as triple-negative breast cancer (TNBC) models. 22 Therefore, we utilized this strain for further modification and development of recombinant variants expressing murine IL-15 (LIVP-IL15-RFP) or murine IL-15Rα (LIVP-IL15Ra-RFP) with deletion of thymidine kinase (TK) to treat 4T1 murine breast cancer model, which represents a highly immunosuppressive tumor model, and CT26 murine colon carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in massive sequencing technologies over the past decade have allowed for a better understanding of the genetic relationships between different smallpox vaccines [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In this context, the complete genomic sequencing of Lister, IOC and Dryvax vaccine strains showed high genetic diversity among clonal isolates obtained from a single vaccine vial, especially in the genome ends where virulence genes are located [ 12 , 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%